2009
DOI: 10.1002/gcc.20699
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics reveals mechanisms of copy number alterations responsible for transcriptional deregulation in colorectal cancer

Abstract: To evaluate the mechanisms and consequences of chromosomal aberrations in colorectal cancer (CRC), we used a combination of spectral karyotyping, array comparative genomic hybridization (aCGH), and array-based global gene expression profiling on 31 primary carcinomas and 15 established cell lines. Importantly, aCGH showed that the genomic profiles of primary tumors are recapitulated in the cell lines. We revealed a preponderance of chromosome breakpoints at sites of copy number variants (CNVs) in the CRC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 39 publications
8
79
0
2
Order By: Relevance
“…4). FGFR2 has been found to be amplified and overexpressed in the colon cancer cell line H716 (13). We found that ponatinib potently inhibited the growth of H716 cells with a GI 50 value of 7 nmol/L but did not affect the growth of Colo205 cells (430 nmol/L; Fig.…”
Section: Activity Of Ponatinib In Gastric Cancer Models With Fgfr2 Ammentioning
confidence: 64%
See 1 more Smart Citation
“…4). FGFR2 has been found to be amplified and overexpressed in the colon cancer cell line H716 (13). We found that ponatinib potently inhibited the growth of H716 cells with a GI 50 value of 7 nmol/L but did not affect the growth of Colo205 cells (430 nmol/L; Fig.…”
Section: Activity Of Ponatinib In Gastric Cancer Models With Fgfr2 Ammentioning
confidence: 64%
“…FGFR2 is amplified in 4% of breast cancers (5,8), 3% to 25% of gastric cancers (9)(10)(11)(12) and in colon cancer (13,14). In addition, activating mutations in FGFR2 and FGFR3 have been found in 10% of endometrial cancers (15)(16)(17) and about 60% of nonmuscle-invasive bladder tumors (18,19), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have surveyed DNA copy number alterations (CNAs) in CRC, establishing that CIN tumors harbor numerous broad gains and losses, often affecting whole chromosome arms; common alterations include gain of chromosome arms 7p (EGFR), 8q (MYC), 11p, 13q, and 20q and loss of 1p, 4q, 5q (APC), 8p, 17p (TP53), and 18q (DCC, SMAD4) (10)(11)(12)(13). Because of the large number of genes spanned by most of these alterations, pinpointing new driver cancer genes has proven challenging.…”
mentioning
confidence: 99%
“…Its expression behavior is down regulating in cold thyroid nodules (CTNs) as reported [28]. GPM6A is not yet found with thyroid cancer.…”
Section: X-axis: Cancer Typesmentioning
confidence: 73%